2006
DOI: 10.2174/138945006776818719
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates and Epithelial Repair - More Than Just Post-Translational Modification

Abstract: Epithelia are the layers of cells that form barriers between external milieu and underlying tissues and thus, are important components of most organs of the body. Epithelial layers of organs, such as the lung, are exposed to various challenges resulting in frequent injury. Epithelial wound healing represents an important process by which repair restores the physical barrier lost as a result of cell damage and apoptosis. The repair of epithelial layers consists of a series of ordered events including epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Glycated proteins act through receptors of AGEs activating pathways, the NF-kB-mediated inflammation pathway, and ERK-and PI3K/Akt signalling [141]. The link between carbohydrates and epithelial repair suggests that glycation events may have deleterious effects [142]. Studies have revealed that more AGEs are concentrated, the less keratinocytes will be activated.…”
Section: Re-epithelialization In Chronic Wounds: When Problems Arisementioning
confidence: 99%
“…Glycated proteins act through receptors of AGEs activating pathways, the NF-kB-mediated inflammation pathway, and ERK-and PI3K/Akt signalling [141]. The link between carbohydrates and epithelial repair suggests that glycation events may have deleterious effects [142]. Studies have revealed that more AGEs are concentrated, the less keratinocytes will be activated.…”
Section: Re-epithelialization In Chronic Wounds: When Problems Arisementioning
confidence: 99%
“…A review of these effects has been published recently, 54 and the link between carbohydrates and epithelial repair has been studied in great detail. 55 The fact that AGEs also modify dermal fibroblast proliferation 56 underlines the clinical observation of extremely difficult wound care in patients with diabetes. These pathways are integrated via the highly conserved mTOR 30 and represent important signaling cascades in wound healing and pathogenesis.…”
Section: Re-epithelializationmentioning
confidence: 99%
“…Increased presentation of sLex was observed in areas of epithelial damage relative to areas of intact epithelium. In an in vitro model of bronchial epithelial repair, cell surface expression of sLex was shown to be significantly increased following mechanical injury of airway epithelial cell monolayers and inhibition of sLex completely prevented repair [86]. Further studies demonstrated that sLex decoration of epidermal growth factor receptor (EGFR) plays an important role in mediating airway epithelial wound repair [87].…”
Section: Role Of Cell Surface Glycoconjugates In Epithelial Repairmentioning
confidence: 99%